Populations of Orchis militaris, Epipactis palustris and Malaxis monophyllos in the Republic of Mordovia (Central Russia) - Khapugin, Anatoliy A.; Silaeva, Tatyana B.; Semchuk, Anastasia A.; Kunaeva, Elena N. (Biodiversity: Research and Conservation, 2016)
Population-based studies of endangered plant species are key methods for assessment of the status for these plants at any territory. Plant species of the Orchidaceae family are sensitive components in natural ecosystems. That is why determination of the status for their populations can be considered as indicators for the status of natural ecosystem position as a whole. Investigations of three Orchidaceae species populations (Orchis militaris L., Epipactis palustris (L.) Crantz, Malaxis monophyllos (L.) Swartz) were carried out in Central Russia (Republic of Mordovia). Abundance, density, structure and dynamics of populations of these species were studied. Species composition of accompanying flora was established for each rare species. Some morphometrical parameters of individuals for the studied species were measured. Features of ontogenetic spectrum for Orchis militaris and Epipactis palustris populations were shown.